Ceramide metabolism alterations contribute to Tumor Necrosis Factor-induced melanoma dedifferentiation and predict resistance to immune checkpoint inhibitors in advanced melanoma patients - Dufau, Carine; Genais, Matthieu; Mucher, Elodie; Jung, Benjamin; Garcia, Virginie; Montfort, Anne; Tosolini, Marie; Clarke, Christopher J.; Medin, Jeffrey A.; Levade, Thierry; Delord, Jean-Pierre; Meyer, Nicolas; et al. (Frontiers in Immunology, 2024)
Introduction: Advanced cutaneous melanoma is a skin cancer characterized by a poor prognosis and high metastatic potential. During metastatic spread, melanoma cells often undergo dedifferentiation toward an invasive phenotype, resulting in reduced expression of microphthalmia-associated transcription factor (MITF)-dependent melanoma antigens and facilitating immune escape. Tumor Necrosis Factor (TNF) is known to be a key factor in melanoma dedifferentiation. Interestingly, accumulating evidence suggests that TNF may play a role in melanoma progression and resistance to immunotherapies. Additionally, TNF has been identified as a potent regulator of sphingolipid (SL) metabolism, which could contribute to melanoma aggressiveness and the process of melanoma dedifferentiation. Methods: We conducted RNA sequencing and mass spectrometry analyses to investigate TNFinduced dedifferentiation in two melanoma cell lines. In vitro experiments were performed to manipulate sphingolipid metabolism using genetic or pharmacologic alterations in combination with TNF treatment, aiming to elucidate the potential involvement of this metabolism in TNF-induced dedifferentiation. Lastly, to evaluate the clinical significance of our findings, we performed unsupervised analysis of plasma sphingolipid levels in 48 patients receiving treatment with immune checkpoint inhibitors, either alone or in combination with anti-TNF therapy. Results: Herein, we demonstrate that TNF-induced melanoma cell dedifferentiation is associated with a global modulation of sphingolipid metabolism. Specifically, TNF decreases the expression and activity of acid ceramidase (AC), encoded by the ASAH1 gene, while increasing the expression of glucosylceramide synthase (GCS), encoded by the UGCG gene. Remarkably, knockdown of AC alone via RNA interference is enough to induce melanoma cell dedifferentiation. Furthermore, treatment with Eliglustat, a GCS inhibitor, inhibits TNF-induced melanoma cell dedifferentiation. Lastly, analysis of plasma samples from patients treated with immune checkpoint inhibitors, with or without anti-TNF therapy, revealed significant predictive sphingolipids. Notably, the top 8 predictive sphingolipids, including glycosphingolipids, were associated with a poor response to immunotherapy. Discussion: Our study highlights that ceramide metabolism alterations are causally involved in TNFinduced melanoma cell dedifferentiation and suggests that the evolution of specific ceramide metabolites in plasma may be considered as predictive biomarkers of resistance to immunotherapy.